Participation of Islamic Religious Information in Preventing the Spread of Covid-19 At Marabahan Prison - Wibisono, Gunawan; Kurniawati, Marhaeni Fajar (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
This study aims to examine the role of Islamic religious instructors in preventing the covid-19 virus. This type of research is field research using a qualitative approach. The research location is the Marabahan Detention Center, Barito Kuala Regency. The results of this study: (1) In the process of restoring social relations, of course, the role of religious instructors is very important, especially in this new normal period, people still feel scared and worried about the current epidemic that is hitting Indonesia, causing a rift in public relations, which they usually interact with each other but since the current outbreak has forced them to reduce their activities outside the home, (2) The role of Islamic religious instrutors in preventing the covid-19 virus through lectures, and dialogues in places of worship with limited participants and through social media Facebook and Instagram, (3) The supporting factor is employee awareness. The inhibiting factor is because of the government's prohibition on gathering.